2014
DOI: 10.1002/mrm.25457
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of transverse signal decay with application to human brain

Abstract: Purpose: Transverse relaxation analysis with several signal models has been used extensively to determine tissue and material properties. However, the derivation of corresponding parameter values is notoriously unreliable. We evaluate improvements in the quality of parameter estimation using Bayesian analysis and incorporating Rician noise, as appropriate for magnitude MR images. Theory and Methods: Monoexponential, stretched exponential, and biexponential signal models were analyzed using nonlinear least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Our results are in agreement with the previous work of Neil and Bretthorst (27) and Bouhrara et al (31) which showed improved accuracy and precision in the estimation of the diffusion and transverse relaxation parameters, respectively, from two-component signal models through use of Bayesian-based approaches compared to NLLS-based methods. In addition, the Bayesian analysis that we have outlined is widely applicable and has great potential to improve the quality of derived MWF from other MRI techniques, such as gradient recalled echo- or other steady state-based analyses (47-49, 50).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in agreement with the previous work of Neil and Bretthorst (27) and Bouhrara et al (31) which showed improved accuracy and precision in the estimation of the diffusion and transverse relaxation parameters, respectively, from two-component signal models through use of Bayesian-based approaches compared to NLLS-based methods. In addition, the Bayesian analysis that we have outlined is widely applicable and has great potential to improve the quality of derived MWF from other MRI techniques, such as gradient recalled echo- or other steady state-based analyses (47-49, 50).…”
Section: Discussionsupporting
confidence: 93%
“…Bayesian analysis can be particularly robust for parameter estimation in models with several unknown parameters, especially in the presence of noise (27-31). Unlike NLLS, it does not require initial estimates and so is much less susceptible to problems with local minima.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For mcDESPOT, the bSSFP signals were generated for FAs of θ ° = {2, 6, 14, 22, 30, 38, 46, 54, 62, 70} and TR bSSFP = 6.5 ms, while the SPGR signals were generated for FAs of θ ° = {2, 4, 6, 8, 10, 12, 14, 16, 18, 20} and TR SPGR = 6.5 ms. For CPMG, signals were generated for 32 echoes with TE increasing linearly from 8 to 256 ms. All simulations used input parameters T 2, s = 15 ms, T 2, l = 90 ms, T 1, s = 450 ms, and T 1, l = 1400 ms; these are based on reported values from human brain imaging (14,7,8,16,17,24). All numerical calculations were performed using routines developed inhouse with MATLAB (MathWorks, Natick, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, analyses of factors that result in signal deviation from the ideal SPGR and bSSFP models are needed. These factors include diffusion [20, 21], magnetization transfer [22], signal modeling [23], magnetization spoiling [24, 25], magic angle effects [26], internal gradients [27, 28] and noise distribution [29, 30]. Nevertheless, the present work stands to indicate the feasibility of high quality in-vivo HR mapping of PgWF in articular cartilage of the human knee joint in an acceptable clinical acquisition time through use of BMC-mcDESPOT.…”
Section: Discussionmentioning
confidence: 99%